IN VITRO ANTIOXIDANT ACTIVITY TEST OF ETHANOL EXTRACT OF PINK CHRYSANTHEMUM LEAVES (CHRYSANTHEMUM MORIFOLIUM) USING DPPH AND FRAP METHODS - Nathin Loria , Saragih; Billy Johnson Kepel; Fona Dwiana Hermina Budiarso; Fatimawali Fatimawali; Aaltje Ellen Manampiring (Riviera Publishing, 2025)
Non-communicable diseases (NCDs) are a major global health concern, with degenerative diseases accounting for >80% of premature deaths. The combination of lifestyle and environmental factors increases the production of free radicals in the body, which, when uncontrolled, cause oxidative stress that significantly contributes to various diseases. Antioxidants play a key role in stopping free radical chain reactions. Although the body has endogenous antioxidants, additional exogenous antioxidants are also needed. One source of exogenous antioxidants is pink chrysanthemum leaves, commonly known as an ornamental plant, which shows potential as an antioxidant source. This study aims to analyze phytochemical content and antioxidant activity of pink chrysanthemum leaf ethanol extract using DPPH and FRAP methods, compared with ascorbic acid. This study used laboratory experimental methods. The qualitative color tests for phytochemical screening. Antioxidant activity tested via DPPH and FRAP methods using UV-Vis spectrophotometer at 517 and 739 nm wavelengths. Results : Phytochemical screening showed positive results for steroids, tannins, phenols, flavonoids, saponins, and alkaloids. DPPH method, analyzed using regression line equation Y = 0.3547x + 45.267, showed IC50 13.344, while the ascorbic acid's 3.030. FRAP method, analyzed using regression line equation Y = 0.773x – 27.6, showed IC50 100.388, while the ascorbic acid's 18.174. The ethanol extract of pink chrysanthemum leaves contains steroids, tannins, phenols, flavonoids, saponins, and alkaloids, and possesses antioxidant activity that falls into the very strong category using the DPPH method and the strong category using the FRAP method.